The Influence of Museum Interior Design on Human Behavior - Alfinatur - Rochmah; Sunarmi Sunarmi (Pendhapa, 2022)
Tourism development is essentially an effort to develop and utilize tourist objects and attractions that are realized, among others, in the form of beautiful natural wealth, diversity of flora and fauna, a plurality of cultural traditions and arts, and ancient relics. One of the cultural assets that become a tourist attraction is the museum. The museum is a legal institution helpful in preserving, maintaining, and providing knowledge about historical records to the general public. One of them is the Bukuran Cluster Museum located in Surakarta City and is one of the supporting museums of the Sangiran Museum, which is rich in human fossils. The museum's interior's technical requirements include the collection's arrangement, including exhibition layout, lighting, labels, air conditions, audiovisual equipment, paintings/dioramas, security, and circulation. Thus, this study is an analysis to determine the influence of the interior design of the Bukuran Cluster Museum on human behavior through the physical condition of the museum, as mentioned by the Directorate of Museums.